Revitalizing Customer Satisfaction in Indonesia's Rice Industry: Revitalisasi Kepuasan Pelanggan di Industri Beras Indonesia - Pratama, Muchammad Ikbal; Sulistiyowati, Wiwik; Cahyana , Atikha Sidhi; Putra, Boy Isma (Universitas Muhammadiyah Sidoarjo, 2024)
CV. Central Karya Jaya, a rice distribution company, faced a 40% profit decline. This study aims to enhance company performance and customer satisfaction using the Balanced Scorecard and Importance Performance Analysis (IPA). Data from 70 respondents showed a financial ROE above 12%, but customer satisfaction had a 72.25% conformity, revealing unmet needs. Key improvements are needed in managerial friendliness, employee responsiveness, and personalized service. Recommendations include fostering better employee relations and understanding customer needs, with future research suggesting the use of Quality Function Deployment (QFD) for further service enhancement. Highlights: Financial Performance: ROE above 12% indicates solid financial health. Customer Satisfaction: 72.25% conformity shows areas needing improvement. Key Improvements: Enhance managerial friendliness and employee responsiveness Keywords: Performance Measurement, Balanced Scorecard, Customer Satisfaction, Rice Distribution, Importance Performance Analysis